2014
DOI: 10.1155/2014/461728
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Potential Use of Cuttlefish Skin Gelatin Hydrolysates Prepared by Different Microbial Proteases

Abstract: Composition, functional properties, and in vitro antioxidant activities of gelatin hydrolysates prepared from cuttlefish skin were investigated. Cuttlefish skin gelatin hydrolysates (CSGHs) were obtained by treatment with crude enzyme preparations from Bacillus licheniformis NH1, Bacillus mojavensis A21, Bacillus subtilis A26, and commercial alcalase. All CSGHs had high protein contents, 74.3–78.3%, and showed excellent solubility (over 90%). CSGH obtained by alcalase demonstrated high antioxidant activities m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 45 publications
(74 reference statements)
5
44
0
3
Order By: Relevance
“…Gly, Pro and Ala were dominant hydrophobic amino acids in HC. Hydrophobic amino acids have been found in several antioxidative peptides (Jridi et al ., ; Sae‐Leaw et al ., ; Karnjanapratum et al ., ). Jridi et al .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Gly, Pro and Ala were dominant hydrophobic amino acids in HC. Hydrophobic amino acids have been found in several antioxidative peptides (Jridi et al ., ; Sae‐Leaw et al ., ; Karnjanapratum et al ., ). Jridi et al .…”
Section: Resultsmentioning
confidence: 97%
“…Gly, Pro and Ala were dominant hydrophobic amino acids in HC. Hydrophobic amino acids have been found in several antioxidative peptides (Jridi et al, 2014;Sae-Leaw et al, 2016b;Karnjanapratum et al, 2017). Jridi et al (2014) found that the cuttlefish skin hydrolysate with the higher ratio of hydrophobic amino acids had the higher antioxidative activities.…”
Section: Resultsmentioning
confidence: 99%
“…Effectively, several researchers groups, have been able to generate various biological activities from different marine proteins in vitro [7][8][9] and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Protein hydrolysates come as an alternative to synthetic antioxidants. In fact, protein hydrolysates derived from many fish species such as goby [4], cuttlefish [11], sardinella [12] and zebra blenny [13] have demonstrated antioxidative activities.…”
Section: Introductionmentioning
confidence: 99%